The Influence of Farmers' Welfare on Oil Palm Plantation Productivity in Indonesia - Pretty Luci Lumbanraja; Penny Charity Lumbanraja; Aprian Wahyu Muttaqin; Shalehah Istiqomah Samal (Indonesian Journal of Agricultural Research, 2023)
Farmers, especially oil palm farmers, contribute greatly to the palm oil industry and the national economy. Strategic agendas to increase the productivity of oil palm plantations, such as land certification programs for the people, agrarian reform, social forestry, and rejuvenation of smallholder plantations, will be hampered if farmers' welfare is ignored. This research aims to determine the influence of variables measuring farmer welfare on palm oil productivity. This exploratory research uses inferential analysis techniques. The data used is secondary data in the form of a time series for the 2015-2021 period. This research uses simple linear regression statistical data analysis with the Structural Equation Model (SEM) with the alternative Partial Least Square (PLS) method. The research results show that farmer welfare has a significant positive effect on oil palm productivity (0.000) < (0.005) with an estimated size of 0.910. In the sense that there is a positive and significant influence on farmer welfare on palm oil productivity.